FIRST OBSERVATION AT THE TÜBITAK TURKISH NATIONAL OBSERVATORY - Keskin, V.; Aslan, Z. (Одеські астрономічні публікації, 2017)
The B, V and R light curves of well-known close binary W UMa were obtained at the newly constructed TÜBITAK Turkish National Observatory which located approximately 50 kilometers north of Antalya city. 40 cm telescope donated by Utrecht University was used during the observations. Comparison and check star’s observations versus air mass and Check minus Comparison values are presented.